Enlightening the contribution of the dark matter to the X chromosome inactivation process in mammals. (August 2016) - Casanova, Miguel; Liyakat Ali, Tharvesh Moideen; Rougeulle, Claire
Abstract: X-chromosome inactivation (XCI) in mammals represents an exceptional example of transcriptional co-regulation occurring at the level of an entire chromosome. XCI is considered as a means to compensate for gene dosage imbalance between sexes, yet the largest part of the chromosome is composed of repeated elements of different nature and origins. Here we consider XCI from a repeat point of view, interrogating the mechanisms for inactivating X chromosome-derived repeated sequences and discussing the contribution of repetitive elements to the silencing process itself and to its evolution.